Dealing with multiple organ failure - Karel Morlans Hernández; José Santos Gracia; Carlos M. González-Prendes Álvarez; Fausto Rodríguez Salgueiro; Bruno García Mendive; Humberto Saínz (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2014)
One of the greatest challenges faced by physicians in an ICU is multiple organ failure, syndrome that shows unclear multifactor etiopathogenesis, varied clinical picture, few early diagnosis devices, high mortality rate and non-specific treatment so far. This paper reviews these aspects so as to update the Knowledge of our cardiologists who very often face this interesting but deadly syndrome in ICUs.